Stromal-Cell-Derived Factor-1 (SDF-1)/CXCL12 as Potential Target of Therapeutic Angiogenesis in Critical Leg Ischaemia - Teik K. Ho; X. Shiwen; D. Abraham; J. Tsui; D. Baker (Cardiology Research and Practice)
In the Western world, peripheral vascular disease (PVD) has a high prevalence with high morbidity and mortality. In a large percentage of these patients, lower limb amputation is still required. Studies of ischaemic skeletal muscle disclosed evidence of endogenous angiogenesis and adaptive skeletal muscle metabolic changes in response to hypoxia. Chemokines are potent chemoattractant cytokines that regulate leukocyte trafficking in homeostatic and inflammatory processes. More than 50 different chemokines and 20 different chemokine receptors have been cloned. The chemokine stromal-cell-derived factor-1 (SDF-1 aka CXCL12) is a constitutively expressed and inducible chemokine that regulates multiple physiological processes, including embryonic development and organ homeostasis. The biologic effects of SDF-1 are mediated by chemokine receptor CXCR4, a 352 amino acid rhodopsin-like transmembrane-specific G protein-coupled receptor (GPCR). There is evidence that the administration of SDF-1 increases blood flow and perfusion via recruitment of endothelial progenitor cells (EPCs). This review will focus on the role of the SDF-1/CXCR4 system in the pathophysiology of PVD and discuss their potential as therapeutic targets for PVD.